Jogadores ou Espectadores? Pontos de vista no cinema e nos videojogos - Luz, Filipe Costa (2009)
In this work we intent to explore similarities or differences between the point of view in cinema and video games. The issue that we will explore is what type of relations we can discover in camera angles and film plane definitions with first, third and god point-of view in videogames.